Endoscopic Browplasty - Lee, Heather; Quatela, Vito C. (Facial Plastic Surgery, 2018)
The endoscopic brow lift has become an established procedure that can safely and reliably rejuvenate the upper third of the face. The authors discuss relevant anatomy and considerations for patient selection to optimize surgical outcomes. A detailed review of surgical technique is presented, and the potential complications and means to reduce them are discussed.
Keywords: endoscopic brow lift; browplasty; forehead rejuvenation